Liquid composition and optical film
By using a specific composition of the liquid composition, the problem of dirt and the surface status of the solid layer is not good during heating and drying, and the effect of reducing dirt and improving the surface state of the curing layer.
Patent Information
- Application Number
- CN202380049863.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-28
- Filing Date
- 2023-07-10
- Publication Date
- 2025-01-28
AI Technical Summary
The prior art is prone to resin-like dirt when heating and drying the liquid composition, resulting in contamination of the optical film and frequent stopping of the production line, and the surface state of the cured layer is poor.
The liquid composition containing a non -ionic surface active agent and water that contains the average molecular weight of the number is greater than 500. Compared with the weight of the non -ionic surfactant, the average molecular weight is more than 100 or less than 500.
The dirt in the heating and drying device is reduced, the cleaning frequency is reduced, the stop time of the production line is shortened, and the surface status of a good curing layer is obtained.
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The present invention relates to a liquid composition and an optical film. Background Art
[0002] Optical films can be provided with various functions by being made into films having a multilayer structure. The multilayer structure is sometimes formed by a method including a step of coating a liquid composition on the surface of a film serving as a substrate. In order to reduce the orientation defects of the added liquid crystal compound and to make the layer of the liquid composition function as an antistatic layer, a surfactant is sometimes added to the liquid composition (see Patent Documents 1 to 3).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2017-203168 (corresponding foreign publication: U.S. Patent Application Publication No. 2018 / 0002459);
[0006] Patent document 2: International Publication No. 2016 / 136231 (corresponding foreign publication: U.S. Patent Application Publication No. 2017 / 0351147);
[0007] Patent document 3: Japanese Patent Application Publication No. 2011-184676. Summary of the invention
[0008] Problem that the invention aims to solve
[0009] In recent years, there is a demand for aqueous liquid compositions containing water as a medium because of their low environmental burden. An aqueous liquid composition is applied to the surface of a film forming a substrate to form a layer of the liquid composition, and the layer is dried to remove water, thereby obtaining an optical film having a multilayer structure containing a solidified layer of the liquid composition.
[0010] When a heating and drying device is used to dry a layer of a liquid composition, resinous dirt may sometimes adhere to the inside of the heating and drying device. The dirt inside the heating and drying device may cause contamination of the optical film, which is required to be of high quality. Therefore, in order to clean the dirt inside the heating and drying device, the production line of the optical film may be frequently stopped. Therefore, a liquid composition that generates less dirt during drying is required.
[0011] Furthermore, for an optical film, a cured layer of a liquid composition is required to have a good surface state.
[0012] Therefore, there is a demand for a liquid composition that generates little dirt during drying and can provide a cured layer with a good surface condition, and an optical film including a cured layer of the liquid composition.
[0013] Solutions for solving problems
[0014] The present inventors have conducted intensive research to solve the above-mentioned problems. As a result, they have found that the resinous dirt generated inside the heating and drying device comes from the surfactant contained in the liquid composition. Based on this understanding, the present inventors have conducted further research and found that the above-mentioned problems can be solved by the following liquid composition, thereby completing the present invention. The above-mentioned liquid composition contains a nonionic surfactant with a number average molecular weight greater than 500 and water, and the component with a number average molecular weight of 100 or more and 500 or less is less than a specified weight relative to the weight of the above-mentioned nonionic surfactant.
[0015] That is, the present invention provides the following contents.
[0016] [1] A liquid composition comprising 70 parts by weight or more and 100 parts by weight or less of a nonionic surfactant having a number average molecular weight greater than 500, 0 parts by weight or more and 30 parts by weight or less of a component having a number average molecular weight of 100 or more and 500 or less, and water.
[0017] [2] The liquid composition according to [1], wherein the number average molecular weight of the nonionic surfactant is 550 or more.
[0018] [3] The liquid composition according to [1] or [2], wherein the liquid composition contains 0.02% by weight or more and 0.10% by weight or less of the nonionic surfactant.
[0019] [4] The liquid composition according to any one of [1] to [3], further comprising polyurethane and silica particles.
[0020] [5] An optical film comprising a substrate and a cured layer of the liquid composition according to any one of [1] to [4] provided on a main surface of the substrate.
[0021] [6] The optical film according to [5], wherein the substrate is made of a cycloolefin-based resin.
[0022] Effects of the Invention
[0023] According to the present invention, there can be provided a liquid composition which generates little dirt during drying and can provide a cured layer having a good surface condition; and an optical film having a cured layer including the liquid composition. DETAILED DESCRIPTION
[0024] The present invention is described in detail below by showing embodiments and examples. However, the present invention is not limited to the embodiments and examples shown below, and can be arbitrarily changed without departing from the scope of the claims of the present invention and the scope equivalent thereto. The constituent elements of the embodiments shown below can be appropriately combined.
[0025] In the following description, "long strip" refers to a film having a length of more than 5 times the width, preferably 10 times or more, and specifically refers to a film having a length that can be stored or transported by being wound into a roll. The upper limit of the length of the film is not particularly limited, for example, it can be less than 100,000 times relative to the width.
[0026] In the following description, unless otherwise stated, the in-plane retardation Re of the layer is the value represented by Re=(nx-ny)×d. In addition, unless otherwise stated, the retardation Rth in the thickness direction of the layer is the value represented by Rth=[{(nx+ny) / 2}-nz]×d. Here, nx represents the refractive index in the direction perpendicular to the thickness direction of the layer (in-plane direction) and in the direction that gives the maximum refractive index. Ny represents the refractive index of the layer in the above-mentioned in-plane direction and in the direction orthogonal to the nx direction. Nz represents the refractive index in the thickness direction of the layer. d represents the thickness of the layer. Unless otherwise stated, the measurement wavelength is 590nm.
[0027] [1. Liquid composition]
[0028] [1.1. Overview of liquid composition]
[0029] The liquid composition of one embodiment of the present invention contains 70 parts by weight or more and 100 parts by weight or less of a nonionic surfactant having a number average molecular weight greater than 500, 0 parts by weight or more and 30 parts by weight or less of a component having a number average molecular weight of 100 or more and 500 or less, and water.
[0030] Hereinafter, a nonionic surfactant having a number average molecular weight of more than 500 is referred to as a nonionic surfactant (N), and a component having a number average molecular weight of 100 to 500 is referred to as a component (L).
[0031] In other words, the liquid composition according to one embodiment of the present invention may be the liquid composition of the following [1] or [2].
[0032] (1) A liquid composition comprising a nonionic surfactant (N) having a number average molecular weight of more than 500 and water, and excluding a component having a number average molecular weight of 100 to 500.
[0033] (2) A liquid composition comprising 70 parts by weight or more and less than 100 parts by weight of a nonionic surfactant (N) having a number average molecular weight of more than 500, more than 0 parts by weight and less than 30 parts by weight of a component having a number average molecular weight of more than 100 and less than 500, and water.
[0034] The liquid composition of the present embodiment is not easy to generate volatile dirt when it is applied to a substrate to form a layer of the liquid composition and the layer of the liquid composition is heated and dried to solidify. Therefore, it is possible to reduce the pollution of the heating and drying device and reduce the cleaning frequency of the device. As a result, it is possible to shorten the time of stopping the production line and efficiently manufacture a film containing a solidified layer of the liquid composition.
[0035] Furthermore, the components contained in the liquid composition of the present embodiment are well dispersed in the liquid composition, and the cured layer of the liquid composition can have a good surface state.
[0036] [1.2. Nonionic surfactant (N)]
[0037] The nonionic surfactant refers to a surfactant having a hydrophilic group that is generally not ionized in water.
[0038] Examples of nonionic surfactants include acetylene surfactants containing an acetylene structure; compounds having an ester structure of a fatty acid and a polyol; compounds having a polyoxyalkylene structure, etc. Nonionic surfactants may or may not have fluorine atoms, but preferably do not have fluorine atoms because of the small load on the environment.
[0039] Specific trade names of nonionic surfactants include “Surfynol series” manufactured by Air Products & Chemicals, Inc.; “DYNOL 607” manufactured by Nissin Chemical Industry Co., Ltd.; “FLOWLEND-90” and “POLYFLOW KL-900” manufactured by Kyoeisha Chemical Co., Ltd.; “SN-WET 980” and “SN-WET 984” manufactured by San Nopco; “Newcol 170”, “Newcol 85” and “Newcol 3-85” manufactured by Nippon Emulsifier Co., Ltd.; and “NIKKOL” series (BT-7, BT-9, BT-12, BL-4.2, BL-9EX, BB-10, BB-20, BC-7, BC-15, BO-7V, BO-10V, SG-DTD620, SG-DTD630, SG-G2424, PBC-33 and BPS-20) manufactured by Nikko Chemical Co., Ltd. The nonionic surfactant may be used alone or in combination of two or more at any ratio.
[0040] The nonionic surfactant (N) generally has a number average molecular weight of more than 500, preferably 550 or more, and the upper limit is not particularly limited, but may be 15,000 or less.
[0041] Here, the nonionic surfactant (N) may be a compound having no molecular weight distribution, an oligomer, or a polymer. The number average molecular weight of the nonionic surfactant (N) may be measured using gel permeation chromatography (GPC). The measurement conditions may be as follows.
[0042] Injection sample: 0.1 wt% tetrahydrofuran (THF) solution
[0043] Column temperature: 40°C
[0044] Elution solvent: THF
[0045] Detector: Differential Refractometer (RI)
[0046] Standard material: polystyrene
[0047] The HLB value of the nonionic surfactant (N) is not particularly limited, and may be, for example, 7 or more, and, for example, 16 or less. The HLB value can be determined by, for example, the Griffin method.
[0048] The liquid composition of the present embodiment may contain one type of nonionic surfactant (N) alone, or may contain two or more types of nonionic surfactants (N) in combination at any ratio.
[0049] The liquid composition of the present embodiment may or may not contain a surfactant other than the nonionic surfactant (N).
[0050] Taking the liquid composition as 100 weight %, the content of the nonionic surfactant (N) in the liquid composition of the present embodiment is usually greater than 0 weight %, preferably 0.02 weight % or more, preferably 0.10 weight % or less. In the case where the liquid composition contains multiple nonionic surfactants (N), the above content refers to the total content of the multiple nonionic surfactants (N) contained.
[0051] [1.3. Ingredients (L)]
[0052] The liquid composition may or may not contain the component (L) having a number average molecular weight of 100 or more and 500 or less.
[0053] The presence of component (L) in the liquid composition and the weight ratio of the nonionic surfactant (N) to component (L) can be confirmed by GPC. As the GPC conditions, the same conditions as those for measuring the number average molecular weight of the nonionic surfactant (N) can be used.
[0054] The liquid composition may contain only one component (L), or may contain two or more components (L) in combination at any ratio.
[0055] The component (L) may be a substance having no molecular weight distribution, an oligomer, or a polymer.
[0056] In the liquid composition, with respect to the weight ratio of the nonionic surfactant (N) to the component (L), the nonionic surfactant (N) is generally more than 70 parts by weight and less than 100 parts by weight, and the component (L) is generally more than 0 parts by weight and less than 30 parts by weight. Component (L) being more than 0 parts by weight means that component (L) is 0 parts by weight (i.e., excluding component (L)) or greater than 0 parts by weight. Component (L) can be 0 parts by weight, for example, it can also be more than 1 part by weight, for example, it can also be more than 5 parts by weight. The nonionic surfactant (N) is generally less than 100 parts by weight, for example, it can be less than 100 parts by weight. Wherein, the total weight of the nonionic surfactant (N) and component (L) contained in the liquid composition is 100 parts by weight.
[0057] Here, when the liquid composition contains a plurality of nonionic surfactants (N) and / or when the liquid composition contains a plurality of components (L), the weight ratio of the nonionic surfactant (N) to the component (L) is the ratio of the total weight of the nonionic surfactant to the total weight of the component (L).
[0058] The weight ratio of the nonionic surfactant (N) to the component (L) can be determined by measuring GPC of the liquid composition. Specifically, the GPC of the liquid composition is measured, and the weight ratio can be calculated based on the peak area of the nonionic surfactant (N) and the peak area of the component (L), with the area of all peaks being 100%.
[0059] [1.4. Water]
[0060] The liquid composition of the present embodiment usually includes water. Water can be a solvent or a dispersion medium that dissolves or disperses the components included in the liquid composition. For example, from the viewpoint of making the liquid composition suitable as the viscosity range of the coating liquid used in the coating method and the viewpoint of making the thickness of the solidified layer of the liquid composition to be the desired thickness, the content of the water included in the liquid composition can be appropriately set. The content of the water included in the liquid composition is not particularly limited, and the liquid composition is 100 weight %, for example, more than 90 weight %, for example, more than 91 weight %, for example, more than 92 weight %, for example, less than 99 weight %, for example, less than 98 weight %, for example, more than 92 weight % and less than 98 weight %.
[0061] The liquid composition can be used in a coating method as an aqueous coating liquid containing water as a solvent or a dispersion medium. The aqueous coating liquid has a small environmental load when dried.
[0062] [1.5. Other ingredients]
[0063] The liquid composition of the present embodiment may contain an optional component in addition to the nonionic surfactant (N), water, and the optional component (L).
[0064] The liquid composition may contain a polymer. Examples of polymers that the liquid composition may contain include polyurethane, acrylic polymers, polyesters, polyvinyl acetate, polyvinyl chloride, and polyolefins. These polymers may be homopolymers or copolymers. In addition, the polymer may be a prepolymer having a polymerizable group that can be further polymerized. The liquid composition may contain a single polymer or may contain two or more polymers in any ratio.
[0065] The liquid composition preferably contains polyurethane. By using a liquid composition containing polyurethane, a primer layer can be provided on the substrate. By providing the primer layer between the substrate and a functional layer such as a polarizer layer, the adhesion between the substrate and the functional layer can be improved.
[0066] As the polyurethane, for example, one obtained by reacting (i) a component containing two or more active hydrogen atoms in one molecule with (ii) a polyisocyanate component can be used.
[0067] In addition, as a polyurethane, for example, a polyurethane produced in the following manner can be used: a prepolymer containing an isocyanate group obtained by subjecting the above-mentioned component (i) and the above-mentioned component (ii) to a urethanization reaction is extended using a chain extender, and water is added to form a dispersion, thereby producing. The above-mentioned prepolymer can be obtained by subjecting the above-mentioned component (i) and the above-mentioned component (ii) to a urethanization reaction under the condition of an excess of isocyanate groups. In addition, the above-mentioned urethanization reaction can be carried out in an organic solvent that is inactive to the reaction and has a high affinity for water. Furthermore, the prepolymer can also be neutralized before the above-mentioned prepolymer is extended. In addition, as a chain extension method for a prepolymer containing an isocyanate group, a method of reacting a prepolymer containing an isocyanate group with a chain extender in the presence of a catalyst as needed can be cited. At this time, as a chain extender, water, a water-soluble polyamine, a diol, etc. can be used.
[0068] As the component (i) above, a component having hydroxyl-type active hydrogen is preferred, and for example, a compound having an average of two or more hydroxyl groups in one molecule is preferred.
[0069] (i) Specific examples of the component include polyether polyols.
[0070] Examples of the polyether polyol include: alkylene oxide adducts of polyol compounds; ring-opening (co)polymers of alkylene oxides and cyclic ethers (e.g., tetrahydrofuran); polyethylene glycol, polypropylene glycol, ethylene glycol-propylene glycol copolymers, 1,4-butanediol copolymers; glycols such as ethylene glycol, polytetramethylene glycol, polyhexamethylene glycol, and polyoctamethylene glycol; and the like.
[0071] Examples of the polyol compound that can be used to produce the polyether polyol include ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, 1,2-butanediol, 1,3-butanediol, 2,3-butanediol, 1,4-butanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 2,5-hexanediol, dipropylene glycol, 2,2,4-trimethyl-1,3-pentanediol, tricyclodecanedimethanol, 1,4-cyclohexanedimethanol, 2,2-dimethylpropylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,8-octamethylene glycol, glycerol, and trimethylolpropane.
[0072] The component (i) may be used alone or in combination of two or more at any ratio.
[0073] The component (ii) (i.e., the polyisocyanate component) that reacts with the component (i) may be, for example, a compound containing an average of two or more isocyanate groups per molecule. The compound may be an aliphatic compound, an alicyclic compound, or an aromatic compound.
[0074] As the aliphatic polyisocyanate compound, an aliphatic diisocyanate having 1 to 12 carbon atoms is preferred, and examples thereof include hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, hexamethylene diisocyanate (HDI), and the like.
[0075] The alicyclic polyisocyanate compound is preferably an alicyclic diisocyanate having 4 to 18 carbon atoms, and examples thereof include 1,4-cyclohexane diisocyanate, methylcyclohexylene diisocyanate, isophorone diisocyanate (IPDI), and dicyclohexylmethane diisocyanate (HMDI).
[0076] Examples of the aromatic polyisocyanate include tolylene diisocyanate (TDI), 4,4′-diphenylmethane diisocyanate, and xylylene diisocyanate.
[0077] These (ii) components may be used alone or in combination of two or more at any ratio.
[0078] The above-mentioned (i) component and (ii) component can arbitrarily select and use appropriate components according to the purpose of the optical film of the solidified layer of the liquid composition of the present embodiment. Among them, as the (i) component, it is preferred to use a component with a bond that is not easily hydrolyzed, specifically, a polyether polyol is preferred. The polyurethane using a polyether polyol as the (i) component is called "polyether polyurethane". The polyether polyurethane has an ether bond that is not easily hydrolyzed. Therefore, the polyurethane is not easy to deteriorate in a high humidity environment, and therefore the reduction of adhesion in a high humidity environment can be effectively suppressed.
[0079] In addition, these polyurethanes may contain an acid structure in their molecular structure. The polyurethane containing an acid structure can be dispersed in water even if the amount of surfactant is small, so it is expected to improve the water resistance of the cured layer of the liquid composition. This polyurethane is referred to as a self-emulsifying polyurethane, which means that even without a surfactant, the polyurethane can be dispersed and stabilized in water only by molecular ionicity. In addition, the polyurethane containing an acid structure does not require a surfactant or only requires a small amount of a surfactant, so it has excellent adhesion to the substrate and can maintain high transparency.
[0080] Examples of the acid structure include acidic groups such as carboxyl (-COOH) and sulfonic (-SO3H). In addition, the acid structure may be present in the side chain or at the end of the polyurethane. The acid structure may be used alone or in combination of two or more in any ratio.
[0081] The amount of the acid structure is preferably 20 mgKOH / g or more, more preferably 25 mgKOH / g or more, preferably 250 mgKOH / g or less, and more preferably 150 mgKOH / g or less, based on the acid value in the liquid composition. By making the acid value be above the lower limit of the above range, the water dispersibility of the polyurethane can be made good. In addition, by making the acid value be below the upper limit of the above range, the water resistance of the cured layer of the liquid composition can be made good.
[0082] As a method for introducing an acid structure into a polyurethane, for example, the following method can be cited: a carboxyl group is introduced into a polyether polyol in advance by replacing a part or all of the component (i) with a dimethylolalkanoic acid. Here, as the dimethylolalkanoic acid used, for example, dimethylolacetic acid, dimethylolpropionic acid, dimethylolbutyric acid, etc. can be cited. The dimethylolalkanoic acid can be used alone or in combination of two or more in any ratio.
[0083] Part or all of the acid structure contained in the polyurethane in the liquid composition is preferably neutralized with a non-volatile base. By neutralizing the acid structure, even if the optical film including the cured layer of the liquid composition has a thermal history of being exposed to high temperatures, it is possible to maintain the characteristics as an optical material or to bond with an arbitrary member with a strong adhesive force. In addition, even if the acid structure is neutralized, even if the amount of the surfactant is small, the polyurethane particles can be dispersed in water.
[0084] The proportion of neutralized acid structures in the acid structures contained in the polyurethane is preferably 20% or more, particularly preferably 50% or more. By neutralizing 20% or more of the acid structures, even if the optical film including the cured layer of the liquid composition has a thermal history of being exposed to high temperatures, it is possible to maintain the properties as an optical material and to bond to any member with a strong adhesive force.
[0085] In order to react with the crosslinking agent, the polyurethane preferably contains a polar group. As the polar group, methylol, carboxyl, carbonyloxycarbonyl, epoxy, hydroxyl, oxy, ester, silanol, silyl, amino, nitrile, sulfonic etc. can be cited. Methylol, hydroxyl, carboxyl and amino are particularly preferred, hydroxyl and carboxyl are more preferred, and carboxyl is particularly preferred. The amount of the polar group in the polyurethane is preferably 0.0001 equivalent / 1kg or more, more preferably 0.001 equivalent / 1kg or more, and preferably 1 equivalent / 1kg or less.
[0086] As polyurethane, commercially available water-based polyurethane resins can be used. Water-based polyurethane resins are compositions comprising polyurethane and water, and are generally compositions in which polyurethane and any component contained as required are dispersed in water. As water-based polyurethane resins, for example, "ADEKA BONTIGHTER" series made by Aidico, "OLESTER" series made by Mitsui Chemicals, "VONDIC" series made by DIC, "HYDRAN (WLS201, WLS202, etc.)" series, "IMPRANIL" series made by Bayer, "POIZ" series made by Kao Corporation, "SANPRENE" series made by Sanyo Chemical Industries, Ltd., "SUPERFLEX" series made by Daiichi Kogyo Seiyaku Co., Ltd., "NEOREZ" series made by Kusumoto Chemicals, Ltd., "Sancure" series made by Lubrizol, etc. can be used. In addition, polyurethane can be used alone or in combination of two or more in any ratio.
[0087] In the liquid composition, the state of the polyurethane is arbitrary, and it can be dispersed in a particle state or dissolved in other components such as a solvent. In these states, the polyurethane is preferably dispersed in a particle state. In such a case, from the viewpoint of the optical properties of the optical film of the cured layer including the liquid composition, the average particle size of the polyurethane particles is preferably 0.01 μm to 0.4 μm.
[0088] The liquid composition may contain a crosslinking agent. In particular, when the liquid composition contains polyurethane, it is preferred to contain a crosslinking agent.
[0089] The crosslinking agent reacts with the reactive groups of the polyurethane to form bonds, thereby making the polyurethane crosslinked. Through this crosslinking, the mechanical strength, adhesion and moisture and heat resistance of the solidified layer of the liquid composition can be improved. Generally, the crosslinking agent can react with the polar groups contained in the polyurethane such as the carboxyl group and the anhydride group thereof contained as the above-mentioned acid structure, and the hydroxyl group remaining after the reaction of the (i) component and the (ii) component due to unreaction to form a crosslinked structure.
[0090] As the crosslinking agent, for example, a compound having two or more functional groups capable of reacting with the reactive groups of the polyurethane to form a bond in one molecule can be used. As the crosslinking agent, a compound having a functional group capable of reacting with the carboxyl group or its anhydride group of the polyurethane is particularly preferred.
[0091] When giving a specific example of the cross-linking agent, an epoxy compound is mentioned. In addition, the cross-linking agent may be used individually by 1 type, or may be used in combination of 2 or more types at any ratio.
[0092] As the epoxy compound, a multifunctional epoxy compound having two or more epoxy groups in one molecule can be used. As the epoxy compound, an epoxy compound that is soluble in water or can be dispersed in water and emulsified is particularly preferred. If the epoxy compound is soluble in water or can be emulsified, then when the liquid composition is a water-based resin, the coating property of the water-based resin can be improved, so that the solidified layer of the liquid composition can be easily manufactured. Here, the water-based resin refers to a composition containing solid components such as a polymer in a state dissolved or dispersed in a water-based solvent such as water.
[0093] When giving examples of the above-mentioned epoxy compounds, there can be mentioned: diepoxide compounds obtained by etherification of 1 mol of diols such as ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, etc. with 2 mols of epichlorohydrin; polyepoxide compounds obtained by etherification of 1 mol of polyols such as glycerol, polyglycerol, trimethylolpropane, pentaerythritol, sorbitol, etc. with 2 or more mols of epichlorohydrin; diepoxide compounds obtained by esterification of 1 mol of dicarboxylic acids such as phthalic acid, terephthalic acid, oxalic acid, adipic acid, etc. with 2 mols of epichlorohydrin, etc.
[0094] When more specific examples of epoxy compounds are given, 1,4-bis(2′,3′-epoxypropoxy)butane, 1,3,5-triglycidyl isocyanurate, 1,3-diglycidyl-5-(γ-acetoxy-β-oxypropyl)isocyanurate, sorbitol polyglycidyl ethers, polyglycerol polyglycidyl ethers, pentaerythritol polyglycidyl ethers, diglycerol polyglycidyl ether, 1,3,5-triglycidyl (2-hydroxyethyl)isocyanurate, glycerol polyglyceryl ethers and trimethylolpropane polyglycidyl ethers can be mentioned.
[0095] Moreover, when giving an example of a commercial item of an epoxy compound, "Denacol (Denacol EX-521, Denacol EX-512, EX-614B, etc.)" series etc. manufactured by Nagase ChemteX Corporation are mentioned.
[0096] The epoxy compounds may be used alone or in combination of two or more at any ratio.
[0097] Relative to 100 parts by weight of polyurethane, the amount of epoxy compound is usually more than 2 parts by weight, preferably more than 5 parts by weight, more preferably more than 8 parts by weight, usually less than 40 parts by weight, preferably less than 35 parts by weight, more preferably less than 30 parts by weight. By making the amount of epoxy compound more than the lower limit of the above range, the reaction of epoxy compound and polyurethane is fully carried out, so the mechanical strength of the solidified layer of the liquid composition can be appropriately improved. In addition, by making the amount of epoxy compound less than the upper limit, the residue of unreacted epoxy compound can be reduced, and the mechanical strength of the solidified layer of the liquid composition can be appropriately improved.
[0098] In addition, relative to the amount of epoxy compound that is equivalent to the polar group of the polyurethane, the amount of the epoxy compound is preferably 0.2 times or more, more preferably 0.4 times or more, particularly preferably 0.6 times or more, preferably 5.0 times or less, more preferably 4.0 times or less, and particularly preferably 3.0 times or less, based on the weight basis. Here, the amount of epoxy compound that is equivalent to the polar group of the polyurethane refers to the theoretical amount of epoxy compound that can react exactly with the total amount of the polar group of the polyurethane. The polar group of the polyurethane can react with the epoxy group of the epoxy compound. Thus, by controlling the amount of the epoxy compound within the above range, the reaction of the polar group with the epoxy compound can be carried out to an appropriate degree, effectively improving the mechanical strength of the cured layer of the liquid composition.
[0099] The liquid composition may contain a non-volatile base. In particular, when the liquid composition contains polyurethane, it is preferred to contain a non-volatile base.
[0100] Examples of the non-volatile base include bases that are substantially non-volatile under the treatment conditions when the liquid composition is applied to a substrate and then dried. Here, substantially non-volatile generally means that the amount of non-volatile base reduced is 80% or less. In addition, examples of the treatment conditions when the liquid composition is applied to a substrate and then dried include, for example, leaving it at 80° C. for 1 hour. Such a non-volatile base can function as a neutralizer to neutralize the acid structure of the polyurethane.
[0101] As the non-volatile base, an inorganic base or an organic base may be used. An organic base having a boiling point of 100° C. or higher is particularly preferred, an amine compound having a boiling point of 100° C. or higher is more preferred, and an amine compound having a boiling point of 200° C. or higher is particularly preferred. In addition, the organic base may be a low molecular weight compound or a polymer.
[0102] When giving examples of non-volatile bases, examples of inorganic bases include sodium hydroxide and potassium hydroxide. In addition, examples of organic bases include 2-amino-2-methyl-1-propanol (AMP), triethanolamine, triisopropanolamine (TIPA), monoethanolamine, diethanolamine, tri[(2-hydroxy)-1-propyl]amine, 2-amino-2-methyl-1,3-propanediol (AMPD), 2-amino-2-hydroxymethyl-1,3-propane potassium hydroxide, zinc ammonium complex, cuprammonium complex, silver ammonium complex, γ-aminopropyl triethoxysilane, γ-aminopropyl trimethoxysilane, N-β (aminoethyl)-γ-aminopropyl trimethoxysilane, N-β (aminoethyl)-γ-aminopropyl trimethyl dimethoxysilane, N-phenyl-γ-aminopropyl trimethoxysilane, Methoxysilane, N,N-bis(trimethylsilyl)urea, 3-ureidopropyltrimethoxysilane, 3-aminopropyl-tri(2-methoxy-ethoxy-ethoxy)silane, N-methyl-3-aminopropyltrimethoxycarboxylic acid dihydrazide, oxalic acid dihydrazide, malonic acid dihydrazide, succinic acid dihydrazide, adipic acid dihydrazide, sebacic acid dihydrazide, dodecanedioic acid dihydrazide, isophthalic acid dihydrazide, terephthalic acid dihydrazide, quinoline, picoline, pyridine, morpholine, piperazine, cyclohexylamine, hexamethylenediamine, N,N-dimethylformamide, ethylenediamine, diethylenetriamine, tetraethylenepentamine, pentaethylenepentamine, isopropanolamine, N,N-diethylmethanolamine, N,N-di Methylethanolamine, aminoethylethanolamine, N-methyl-N,N-diethanolamine, 1,2-propylenediamine, 1,6-hexamethylenediamine, 2-methylpiperazine, 2,5-dimethylpiperazine, isophoronediamine, 4,4′-dicyclohexylmethanediamine, 3,3′-dimethyl-dicyclohexylmethanediamine, 1,2-cyclohexanediamine, 1,4-cyclohexanediamine, aminoethylethanolamine, aminopropylethanolamine, aminohexylethanolamine, aminoethylpropanolamine, aminopropylpropanolamine, aminohexylpropanolamine, dipropylenetriimidazole, 1-(2-aminoethyl)-2-methylimidazole, 1-(2-aminoethyl)-2-ethylimidazole, 2-aminoimidazole sulfate, 2-(2-
[0063] The present invention also includes 1,3-dimethyl-5-aminopyrazole, 1-isopropyl-5-aminopyrazole, 1-benzyl-5-aminopyrazole, 1,3-dimethyl-5-aminopyrazole, 1-isopropyl-3-methyl-5-aminopyrazole, 1-benzyl-3-methyl-5-aminopyrazole, 1-methyl-4-chloro-5-aminopyrazole, 1-methyl-4-cyano-5-aminopyrazole, 1-isopropyl-4-chloro-5-aminopyrazole, 3-methyl-4-chloro-5-aminopyrazole, 1-benzyl-4-chloro-5-aminopyrazole, amino resins (e.g., 1,3-dimethyl-4-chloro-melamine resin, urea-formaldehyde resin, guanamine resin, etc.). In addition, these may be used alone or in combination of two or more at any ratio.
[0103] The amount of the non-volatile base is usually 0.5 parts by weight or more, preferably 1 part by weight or more, more preferably 2 parts by weight or more, and usually 30 parts by weight or less, preferably 20 parts by weight or less, more preferably 10 parts by weight or less, relative to 100 parts by weight of polyurethane. By making the amount of the non-volatile base more than the lower limit of the above range, sufficient adhesive force can be obtained. In addition, by making the amount of the non-volatile base less than the upper limit of the above range, the fading of the polarizer made of polyvinyl alcohol can be suppressed.
[0104] The liquid composition may also contain particles. In particular, when the liquid composition contains polyurethane, it is preferably composed of particles. By making the liquid composition contain particles, the surface roughness of the solidified layer formed by the solidified material of the liquid composition can be increased. Thus, the slippage of the surface of the solidified layer of the liquid composition can be improved, so that the adhesion of the optical film containing the solidified layer can be prevented and the generation of wrinkles when the optical film is wound can be suppressed.
[0105] As particles, any of inorganic particles and organic particles can be used. Among them, water-dispersible particles are preferably used. When the material of the inorganic particles is cited, for example, inorganic oxides such as silicon dioxide, titanium dioxide, aluminum oxide, zirconium oxide, calcium carbonate, talc, clay, calcined kaolin, calcined calcium silicate, hydrated calcium silicate, aluminum silicate, magnesium silicate, calcium phosphate, etc. can be cited. In addition, when the material of the organic particles is cited, for example, silicone resin, fluororesin, acrylic resin, etc. can be cited. Among these, silicon dioxide is preferred. Silica particles have excellent ability to suppress the generation of wrinkles and transparency, are not easy to produce haze, have no coloring or very little coloring, and therefore have little effect on the optical properties of the optical film of the cured layer containing the liquid composition. In addition, the dispersibility and dispersion stability of silicon dioxide in the liquid composition are good. Among the silicon dioxide particles, amorphous colloidal silicon dioxide particles are particularly preferred.
[0106] The average particle diameter of the particles is usually more than 1nm, preferably more than 5nm, more preferably more than 10nm, usually below 500nm, preferably below 300nm, more preferably below 200nm. By making the average particle diameter of the particles more than the lower limit of the above-mentioned scope, the slip of the solidified layer of the liquid composition can be effectively improved. In addition, by making the average particle diameter of the particles below the upper limit of the above-mentioned scope, the haze of the solidified layer of the liquid composition can be suppressed to be low.
[0107] The amount of the particles is usually 1 part by weight or more, preferably 3 parts by weight or more, more preferably 5 parts by weight or more, and usually 50 parts by weight or less, preferably 40 parts by weight or less, more preferably 30 parts by weight or less, relative to 100 parts by weight of polyurethane. By making the amount of the particles more than the lower limit of the above range, the generation of wrinkles can be suppressed when the optical film of the cured layer containing the liquid composition is wound. In addition, by making the amount of the particles less than the upper limit of the above range, the appearance of the optical film without white turbidity can be maintained.
[0108] Other examples of the optional components that may be included in the liquid composition include heat stabilizers, weather stabilizers, leveling agents, antioxidants, antistatic agents, slip agents, antiblocking agents, antifogging agents, lubricants, dyes, pigments, natural oils, synthetic oils, waxes, and the like.
[0109] As the optional components contained in the liquid composition, one kind may be used alone, or two or more kinds may be used in combination at any ratio.
[0110] The liquid composition may also contain a water-soluble solvent in addition to water. Examples of water-soluble solvents include methanol, ethanol, isopropanol, acetone, tetrahydrofuran, N-methylpyrrolidone, dimethyl sulfoxide, ethylene glycol monomethyl ether, ethylene glycol monobutyl ether, etc. These may be used alone or in combination of two or more in any ratio.
[0111] [1.6. Use of liquid composition]
[0112] The liquid composition can be preferably used as a coating liquid for forming a layer of the liquid composition by a coating method.
[0113] As a method for coating the liquid composition, any method can be used, for example, curtain coating, extrusion coating, roll coating, spin coating, dip coating, rod coating, spray coating, slide coating, print coating, gravure coating, die coating and slit coating.
[0114] The liquid composition can be applied on any layer. For example, the liquid composition can be applied on a substrate made of a resin.
[0115] The solidified layer of the liquid composition can be obtained by heating and drying the layer of the liquid composition to solidify it. Usually, by heating and drying the layer of the liquid composition, water contained in the liquid composition is removed and the layer of the liquid composition is solidified.
[0116] The solidified layer of the liquid composition may directly contain the components contained in the liquid composition without water, or may contain reaction products of the components contained in the liquid composition. For example, the solidified layer of the liquid composition may contain crosslinked products, polymers, condensates, etc. of the components contained in the liquid composition.
[0117] The cured layer of the liquid composition of the present embodiment has a good surface condition. Therefore, the liquid composition can be preferably used as a coating liquid for forming a layer constituting an optical film.
[0118] Furthermore, by providing a solidified layer of the liquid composition between the substrate and any functional layer, it can function as a primer layer that improves the adhesion between the substrate and any functional layer. Therefore, the liquid composition can be preferably used as a coating liquid for forming a primer layer.
[0119] [2.Optical film]
[0120] An optical film according to one embodiment of the present invention includes a substrate and a cured layer of the liquid composition provided on a main surface of the substrate.
[0121] The substrate may be in the form of a strip or a single sheet. In the case of a strip, the operation for providing the solidified layer of the liquid composition can be performed while the substrate is continuously conveyed, so that the optical film can be produced efficiently.
[0122] As the substrate, a resin film containing a resin and formed of a resin can be used. As the resin constituting the substrate, a resin containing any polymer can be used. As the resin constituting the substrate, a thermoplastic resin is particularly preferred, and a cycloolefin resin is particularly preferred. The cycloolefin resin includes a polymer containing an alicyclic structure such as a cycloolefin polymer or its hydrogenate. Hereinafter, the polymer containing an alicyclic structure will also be referred to as an alicyclic structure-containing polymer. The cycloolefin resin is excellent in transparency, low hygroscopicity, dimensional stability, and lightness, and is suitable for optical films.
[0123] In addition, the substrate may be a film having a single-layer structure including only one layer, or a film having a multilayer structure having two or more layers. When the substrate has a multilayer structure, it is preferred that at least one of the layers of the substrate is composed of a cycloolefin resin, and it is particularly preferred that at least one outermost layer of the substrate is composed of a cycloolefin resin.
[0124] The alicyclic structure-containing polymer is a polymer having an alicyclic structure in the structural unit of the polymer, and any one of a polymer having an alicyclic structure in the main chain and a polymer having an alicyclic structure in the side chain can be used. In addition, the alicyclic structure-containing polymer can be used alone or in combination of two or more in any ratio. From the viewpoint of mechanical strength, heat resistance, etc., a polymer containing an alicyclic structure in the main chain is particularly preferred.
[0125] Examples of the alicyclic structure include saturated alicyclic hydrocarbon (cycloalkane) structures, unsaturated alicyclic hydrocarbon (cycloolefin, cycloalkyne) structures, etc. From the viewpoint of mechanical strength, heat resistance, etc., cycloalkane structures and cycloalkene structures are particularly preferred, and cycloalkane structures are particularly preferred.
[0126] The number of carbon atoms constituting the alicyclic structure is preferably 4 or more, more preferably 5 or more, preferably 30 or less, more preferably 20 or less, and particularly preferably 15 or less in each alicyclic structure. This is preferred because the mechanical strength, heat resistance, and moldability of the substrate are highly balanced.
[0127] The ratio of the structural unit having an alicyclic structure in the alicyclic structure-containing polymer can be appropriately selected according to the purpose of use, and is preferably 55% by weight or more, more preferably 70% by weight or more, and particularly preferably 90% by weight or more. When the ratio of the structural unit having an alicyclic structure in the alicyclic structure-containing polymer is within this range, it is preferred from the perspective of transparency and heat resistance of the substrate.
[0128] Examples of alicyclic structure-containing polymers include norbornene polymers, monocyclic cyclic olefin polymers, cyclic conjugated diene polymers, vinyl alicyclic hydrocarbon polymers, and hydrogenated products thereof. Of these, norbornene polymers are preferred because of their good transparency and moldability.
[0129] As the norbornene-based polymer, for example, ring-opening polymers of monomers having a norbornene structure, or ring-opening copolymers of monomers having a norbornene structure and any monomer, or hydrogenates thereof can be cited; addition polymers of monomers having a norbornene structure, or addition copolymers of monomers having a norbornene structure and any monomer, or hydrogenates thereof, etc. Among these, hydrogenates of ring-opening (co)polymers of monomers having a norbornene structure are particularly preferred from the viewpoints of transparency, moldability, heat resistance, low hygroscopicity, dimensional stability, and lightness. Here, "(co)polymer" refers to both polymers and copolymers.
[0130] Examples of the monomer having a norbornene structure include bicyclo[2.2.1]hept-2-ene (common name: norbornene), tricyclo[4.3.0.1 2,5 ]Deca-3,7-diene (common name: dicyclopentadiene), 7,8-benzotricyclo[4.3.0.1 2,5 ]Deca-3-ene (common name: methylenetetrahydrofluorene), tetracyclo[4.4.0.1 2,5 .1 7,10] Dodec-3-ene (common name: tetracyclododecene) and derivatives of these compounds (e.g. compounds having a substituent on the ring). Here, as the substituent, for example, an alkyl group, an alkylene group, a polar group, etc. can be cited. In addition, these substituents may be the same or different, and a plurality of them may be bonded to form a ring. In addition, the monomer having a norbornene structure may be used alone or in combination of two or more in any ratio.
[0131] As the type of polar group, for example, heteroatom or atomic group having heteroatom can be mentioned. As heteroatom, for example, oxygen atom, nitrogen atom, sulfur atom, silicon atom, halogen atom can be mentioned. As specific examples of polar group, carboxyl group, carbonyloxycarbonyl group, epoxy group, hydroxyl group, oxy group, ester group, silanol group, silyl group, amino group, nitrile group, sulfonic acid group and the like can be mentioned.
[0132] As the arbitrary monomer capable of ring-opening copolymerization with the monomer having a norbornene structure, for example, monocyclic olefins such as cyclohexene, cycloheptene, and cyclooctene and their derivatives; cyclic conjugated dienes such as cyclohexadiene and cycloheptadiene and their derivatives, etc. The arbitrary monomer capable of ring-opening copolymerization with the monomer having a norbornene structure may be used alone or in combination of two or more at any ratio.
[0133] The ring-opening polymer of the monomer having a norbornene structure and the ring-opening copolymer with any monomer copolymerizable with the monomer having a norbornene structure can be produced, for example, by polymerizing or copolymerizing the monomer in the presence of a known ring-opening polymerization catalyst.
[0134] As any monomer that can be addition-copolymerized with a monomer having a norbornene structure, for example, α-olefins having 2 to 20 carbon atoms such as ethylene, propylene, and 1-butene and their derivatives; cycloolefins such as cyclobutene, cyclopentene, and cyclohexene and their derivatives; non-conjugated dienes such as 1,4-hexadiene, 4-methyl-1,4-hexadiene, and 5-methyl-1,4-hexadiene, etc. Among these, α-olefins are preferred, and ethylene is more preferred. In addition, any monomer that can be addition-copolymerized with a monomer having a norbornene structure can be used alone or in combination of two or more in any ratio.
[0135] The addition polymer of the monomer having a norbornene structure and the addition copolymer with an arbitrary monomer copolymerizable with the monomer having a norbornene structure can be produced, for example, by polymerizing or copolymerizing the monomer in the presence of a known addition polymerization catalyst.
[0136] Examples of the monocyclic cyclic olefin polymer include addition polymers of a monocyclic cyclic olefin monomer such as cyclohexene, cycloheptene, and cyclooctene.
[0137] Examples of the cyclic conjugated diene polymer include polymers obtained by cyclizing addition polymers of conjugated diene monomers such as 1,3-butadiene, isoprene, and chloroprene; 1,2- or 1,4-addition polymers of cyclic conjugated diene monomers such as cyclopentadiene and cyclohexadiene; and hydrogenated products thereof.
[0138] As the vinyl alicyclic hydrocarbon polymer, for example, polymers of vinyl alicyclic hydrocarbon monomers such as vinyl cyclohexene and vinyl cyclohexane and their hydrogenates; hydrogenates obtained by hydrogenating the aromatic ring part contained in the polymer obtained by polymerizing vinyl aromatic hydrocarbon monomers such as styrene and α-methylstyrene; hydrogenates of aromatic rings of copolymers such as random copolymers or block copolymers of vinyl alicyclic hydrocarbon monomers or vinyl aromatic hydrocarbon monomers and any monomers copolymerizable with these vinyl aromatic hydrocarbon monomers, etc. As the above-mentioned block copolymers, for example, diblock copolymers, triblock copolymers or multi-block copolymers thereof, and tilted block copolymers can also be cited.
[0139] The weight average molecular weight (Mw) of the polymer included in the resin constituting the substrate is usually more than 10000, preferably more than 15000, more preferably more than 20000, usually less than 100000, preferably less than 80000, more preferably less than 50000. Here, the above-mentioned weight average molecular weight is the weight average molecular weight converted using cyclohexane as a solvent, polyisoprene or polystyrene measured by GPC. However, in the case where the sample is not dissolved in cyclohexane, toluene can also be used as the solvent of GPC. When the weight average molecular weight is in such a scope, the mechanical strength of the multilayer film is highly balanced with the molding processability, so it is preferred.
[0140] The molecular weight distribution (weight average molecular weight (Mw) / number average molecular weight (Mn)) of the polymer contained in the resin constituting the substrate is usually more than 1.2, preferably more than 1.5, more preferably more than 1.8, usually less than 3.5, preferably less than 3.0, more preferably less than 2.7. By making the molecular weight distribution more than the lower limit of the above range, the productivity of the polymer can be improved and the cost can be suppressed. In addition, by making the molecular weight distribution less than the upper limit of the above range, the low molecular weight component can be reduced, thereby the relaxation time can be extended. Therefore, the relaxation during high temperature exposure can be suppressed, and the stability of the substrate can be improved.
[0141] The absolute value of the photoelastic coefficient C of the polymer contained in the resin constituting the substrate is preferably 10×10 -12 Pa -1 Below, more preferably 7×10 -12 Pa -1 Below, particularly preferably 4×10 -12 Pa-1 The photoelastic coefficient C is a value represented by "C = Δn / σ" when birefringence is Δn and pressure is σ. By making the photoelastic coefficient of the polymer fall within the above range, the variation of the in-plane retardation Re of the substrate can be reduced.
[0142] The saturated water absorption of the polymer contained in the resin constituting the substrate is preferably 0.03 wt % or less, more preferably 0.02 wt % or less, and particularly preferably 0.01 wt % or less. When the saturated water absorption is within the above range, the time-dependent change of the in-plane retardation Re and the retardation Rth in the thickness direction of the substrate can be reduced.
[0143] The saturated water absorption is a value expressed as a percentage of the mass increased by immersing the test piece in water at a certain temperature for a certain period of time relative to the mass of the test piece before immersion. It is usually measured by immersing in water at 23°C for 24 hours. The saturated water absorption of the polymer can be adjusted to the above range by, for example, reducing the amount of polar groups in the polymer. From the viewpoint of further reducing the saturated water absorption, it is preferred that the above polymer does not have a polar group.
[0144] The resin constituting the substrate may contain any component other than the polymer as long as the effect of the present invention is not significantly impaired. When giving examples of the arbitrary components, the examples include: colorants such as pigments and dyes; plasticizers; fluorescent whitening agents; dispersants; heat stabilizers; light stabilizers; ultraviolet absorbers; antistatic agents; antioxidants; lubricants; surfactants and other additives. These components may be used alone or in combination of two or more in any ratio.
[0145] The amount of the optional component is preferably adjusted so that the amount of the polymer contained in the resin constituting the substrate is usually 50% to 100%, for example 70% to 100%, for example 80% to 100%, for example 90% to 100%.
[0146] Among them, the cycloolefin resin preferably contains substantially no particles. Here, substantially containing no particles means that even if the resin contains particles, the amount of the haze of the substrate can be allowed to increase by less than 0.05% relative to the state of not containing particles at all. There is a tendency for alicyclic structure-containing polymers to lack affinity with most organic particles and inorganic particles. Therefore, when a cycloolefin resin containing particles exceeding the above range is stretched, voids are easily generated, and as a result, a significant increase in haze may occur.
[0147] As described above, the substrate may be a single-layer film layer or a multi-layer film layer having two or more layers. When the substrate is a multi-layer film layer, an optical film having various properties can be manufactured.
[0148] When the substrate has two or more layers, it may have two or more layers of one film layer, or may have two or more different film layers. In addition, a layer composed of a resin other than the above-mentioned cycloolefin resin may be provided on the substrate. As the layer composed of a resin other than the cycloolefin resin, for example, a film layer having functions such as anti-scratch, anti-reflection, antistatic, anti-glare, and antifouling may be cited.
[0149] The total light transmittance of the substrate converted to 1 mm thickness is preferably 80% or more, more preferably 90% or more. The total light transmittance can be measured according to JIS K0115 using a spectrophotometer (UV-visible near-infrared spectrophotometer "V-570" manufactured by JASCO Corporation).
[0150] In addition, the haze of the substrate when it is 1 mm thick is preferably 0.3% or less, more preferably 0.2% or less. Here, the haze is measured at 5 locations according to JIS K7361-1997 using a "turbidimeter NDH-300A" made by Nippon Denshoku Industries, and the average value obtained from these. The average thickness of the substrate is preferably 5 μm or more, more preferably 20 μm or more, preferably 500 μm or less, and more preferably 300 μm or less. The thickness variation range of the substrate is preferably within ±3% of the above average thickness in the length direction and the width direction. By varying the thickness to the above range, the deviation of optical properties such as the delay of the substrate can be reduced.
[0151] The substrate may be an unstretched film that has not been subjected to a stretching treatment, or a stretched film that has been subjected to a stretching treatment. In addition, when the substrate has two or more layers, the film layers that have been subjected to a stretching treatment in advance may be laminated to obtain a stretched film, or a pre-stretched film of a multilayer structure obtained by coextrusion or the like may be subjected to a stretching treatment to obtain a stretched film.
[0152] The substrate may be subjected to energy ray irradiation treatment such as corona discharge treatment, plasma treatment, electron beam irradiation treatment, ultraviolet irradiation treatment, or surface treatment such as chemical treatment. From the perspective of treatment efficiency, corona discharge treatment and plasma treatment are particularly preferred, and corona discharge treatment is more preferred.
[0153] The solidified layer of the liquid composition is a layer obtained by solidifying a layer of the liquid composition.
[0154] As described above, the solidified layer of the liquid composition may directly contain the components contained in the liquid composition without including water, or may contain a reaction product of the components contained in the liquid composition.
[0155] The solidified layer of the liquid composition may be provided on one of the two main surfaces of the substrate, or may be provided on both main surfaces.
[0156] The cured layer of the liquid composition is preferably provided directly on the main surface of the substrate.
[0157] The thickness of the solidified layer of the liquid composition is not particularly limited, and can be, for example, 0.005 μm to 5 μm.
[0158] The optical film can also include any layer except the cured layer of substrate and liquid composition. As the example of any layer, antireflection layer, hard coat layer, antistatic layer, antiglare layer, antifouling layer and interval film can be enumerated. These arbitrary layers can be separately manufactured from the multilayer film with the cured layer of substrate and liquid composition, and laminated with the above-mentioned multilayer film. In addition, any layer can also be further formed on the principal surface of the above-mentioned multilayer film by coating method.
[0159] From the viewpoint of stably exhibiting the function as an optical component, the total light transmittance of the optical film is preferably 80% or more, more preferably 90% or more.
[0160] The haze of the optical film is preferably 5% or less, more preferably 3% or less, and particularly preferably 2% or less. By making the haze a low value, when the optical film is incorporated into a display device, the clarity of the display image of the display device can be improved.
[0161] The optical film may be a phase difference film having a delay in the plane or in the thickness direction. The specific range of the delay can be set according to the purpose of the optical film of the present embodiment. When a specific range is cited, it can usually be appropriately selected from the range of 10nm to 500nm for the in-plane delay Re and -500nm to 500nm for the thickness direction delay Rth.
[0162] [3. Method for producing optical film]
[0163] The above-mentioned optical film can be produced by any method.
[0164] Preferably, the optical film can be manufactured by a method comprising the following steps in sequence: step (1), preparing a substrate; step (2), coating a liquid composition on the main surface of the above-mentioned substrate to form a layer of the liquid composition; and step (3) drying the above-mentioned liquid composition layer to form a solidified layer of the above-mentioned liquid composition.
[0165] The manufacturing method of the substrate is not limited. The substrate is obtained by molding the resin used to form the substrate using a known film forming method. As the film forming method, for example, a casting method, an extrusion molding method and an inflation molding method can be cited. Among them, the melt extrusion method without using a solvent can effectively reduce the amount of residual volatile components, and is preferred from the perspective of the global environment, the perspective of the operating environment and the perspective of excellent manufacturing efficiency. As the melt extrusion method, an inflation molding method using a die head can be cited, and from the perspective of excellent productivity and thickness accuracy, a method using a T die head is particularly preferred.
[0166] When the substrate has two or more layers, the method for manufacturing the substrate is not limited. For example, the substrate can be manufactured by bonding separately manufactured film layers using an adhesive as needed.
[0167] When a substrate having two or more layers is produced without using an adhesive, for example, coextrusion molding methods such as a coextrusion T-die method, a coextrusion inflation method, and a coextrusion lamination method; and film lamination molding methods such as dry lamination can be used.
[0168] Furthermore, a base material having two or more layers can be produced by, for example, a coating molding method in which a solution containing a resin constituting another film layer is coated on the surface of a certain film layer.
[0169] Among these, coextrusion molding is preferred from the viewpoint of manufacturing efficiency and the viewpoint of not leaving volatile components such as solvents in the substrate. Among the coextrusion molding methods, the coextrusion T-die method is particularly preferred. Furthermore, the coextrusion T-die method can include a feed block method and a multi-manifold method, and the multi-manifold method is more preferred from the viewpoint of being able to reduce the deviation of the thickness of each layer.
[0170] As a method of applying the liquid composition onto the main surface of the substrate, any coating method can be used.
[0171] Examples of a method for drying the layer of the liquid composition include natural drying, heat drying, reduced pressure drying, and combinations thereof.
[0172] The liquid composition of the present embodiment generates less dirt when dried. From the viewpoint of effectively utilizing the advantages of the liquid composition of the present embodiment, it is preferably dried by a method including heating a layer of the liquid composition.
[0173] When the layer of the liquid composition is dried by heating, a heating drying device such as an oven can be used. The temperature in the heating drying device is not particularly limited, and is, for example, set to be Tg-30° C. or higher, for example, Tg+30° C. or lower. Here, Tg represents the glass transition temperature of the resin forming the substrate.
[0174] The method for producing an optical film may include any other steps in addition to the above-mentioned steps (1) to (3). As an example of an arbitrary step, there may be mentioned a step of stretching the substrate. When the method for producing an optical film includes a step of stretching the substrate, the substrate may be stretched before step (2), or after step (2), or simultaneously with step (3), or after step (3). When the substrate is stretched after step (2), a layer (e.g., a solidified layer of a liquid composition) disposed on the main surface of the substrate is usually also stretched simultaneously with the substrate.
[0175] The stretching method of the stretched substrate is not particularly limited, and any stretching method can be used. Examples of the stretching method include: a method of uniaxially stretching the film in the longitudinal direction (longitudinal uniaxial stretching method), a method of uniaxially stretching the film in the width direction (transverse uniaxial stretching method), and other uniaxial stretching methods; a biaxial stretching method of stretching the film in the longitudinal direction and in the width direction at the same time, and a sequential biaxial stretching method of stretching the film in one direction of the longitudinal direction and the width direction and then in the other direction; and a method of stretching the film in an oblique direction (oblique stretching method).
[0176] The glass transition temperature of the resin constituting the stretched film is taken as Tg, and the stretching temperature is preferably above (Tg-30°C), more preferably above (Tg-10°C), preferably below (Tg+50°C), and more preferably below (Tg+30°C). The stretching ratio can be appropriately selected according to the optical properties of the substrate used. The specific stretching ratio is usually 1.05 times or more, preferably 1.1 times or more, usually 10.0 times or less, and preferably 2.0 times or less.
[0177] [4. Application of optical film]
[0178] The optical film of this embodiment can be preferably used as, for example, a protective film of an optical element (particularly a polarizer protective film), a phase difference film, or an optical compensation film. In particular, when the cured layer of the optical film is formed into an adhesive layer, the optical film can be bonded to any component with good adhesion.
[0179] Example
[0180] The present invention will be described in detail below with reference to the following examples. However, the present invention is not limited to the following examples, and can be arbitrarily modified without departing from the scope of the claims and their equivalents.
[0181] In the following description, "%" and "parts" indicating amounts are based on weight unless otherwise specified. In addition, unless otherwise specified, the operations described below are performed at room temperature (20°C ± 15°C) and normal pressure (1 atm).
[0182] [Evaluation method]
[0183] (Determination of number average molecular weight, weight ratio of component (L))
[0184] The surfactant compositions used in Examples and Comparative Examples were measured by GPC under the following conditions: During the measurement, a calibration curve was prepared using polystyrene as a standard substance.
[0185] Injection sample: 0.1 wt% tetrahydrofuran (THF) solution
[0186] Column temperature: 40°C
[0187] Elution solvent: THF
[0188] Detector: Differential Refractometer (RI)
[0189] Based on the GPC measurement results, the weight ratio of the component (L) having a number average molecular weight of 100 or more and 500 or less and the number average molecular weight and weight ratio of the surfactant component having a number average molecular weight of more than 500 were determined.
[0190] Specifically, in the chromatograms of the surfactant compositions used in Examples and Comparative Examples, the ratio R of the peak area of the component having a number average molecular weight of 100 or more and 500 or less (when there are multiple peaks, the sum of their areas) is calculated, with the sum of the areas of all peaks being 100%. L (%), and in addition, the ratio R of the peak area of the surfactant component with a number average molecular weight greater than 500 was calculated. N Then, based on these ratios, the weight ratio of the component (L) having a number average molecular weight of 100 or more and 500 or less in the surfactant composition is taken as R L % by weight, the weight proportion of the surfactant component with a number average molecular weight greater than 500 is taken as R N weight%.
[0191] (Dispersibility of Silica Particles and Surface State of Solidified Layer of Liquid Composition)
[0192] The multilayer films obtained in Examples and Comparative Examples were irradiated with high-brightness light (Polarion clean room lamp), and the state of the film surface (surface state) was visually observed.
[0193] The dispersibility of the silica particles was evaluated according to the following criteria.
[0194] Good: The entire film is uniformly and extremely lightly turbid, and the silica particles are uniformly dispersed.
[0195] Acceptable: The film has some thick white turbidity (unevenness), but this is acceptable for practical use.
[0196] Bad: The film has many dark white turbid portions (unevenness).
[0197] A higher evaluation value means that the dispersibility of the silica particles in the liquid composition is higher.
[0198] The surface state of the cured layer of the liquid composition was evaluated according to the following criteria.
[0199] Good: The entire film was uniformly lightly turbid, and no oozing pattern of the surfactant was observed.
[0200] Acceptable: The exudation pattern of the surfactant was observed in the film, but there was no completely turbid portion (falling off).
[0201] Bad: The film has a portion without any turbidity (falling off).
[0202] When there is a portion of the film that is completely free of cloudiness, this means that bubbles were generated when the liquid composition was applied.
[0203] (Residual Ratio of Surfactant in the Cured Layer of Liquid Composition)
[0204] The amount X0 of the surfactant used to produce 1 g of the multilayer film including the substrate (ZEONOR film) was calculated from the thickness of the multilayer film obtained in Examples and Comparative Examples and the amount of the surfactant charged.
[0205] Furthermore, the amount X1 of the surfactant remaining in 1 g of the multilayer film was calculated using the following analysis results. The residual ratio R of the surfactant in the cured layer of the liquid composition was calculated by the following formula.
[0206]
[0207] In addition, the residual rate R is classified according to the following criteria.
[0208] Good: 90%≤R
[0209] Qualified: 70%≤R<90%
[0210] Defective: R<70%
[0211] ·analyze
[0212] 1 g of the multilayer film was weighed in a 500 mL container, 100 mL of cyclohexane was added and left overnight, and then stirred with a magnetic stirrer to dissolve most of the multilayer film to prepare a solution containing a white insoluble component. 50 mL of THF was added to the solution containing the insoluble component, and then methanol was added until the total amount reached about 400 mL to generate a precipitate.
[0213] The precipitate was removed by filtration with folded filter paper, and the solvent was removed by vacuum distillation from the filtrate to obtain a liquid as a methanol-soluble component. The vacuum distillation of the solvent was performed several times using a 100 mL eggplant-shaped flask and an evaporator. The liquid was transferred to a 10 mL volumetric flask, and the solvent: methanol was added to the mark to make up the volume.
[0214] The fixed volume of liquid was filtered through a 0.2 μm filter, transferred to a vial, and the surfactant concentration was determined by HPLC under the following conditions: The surfactant concentration was determined based on a standard curve prepared in advance by analyzing solutions having different surfactant concentrations.
[0215] Based on the obtained surfactant concentration, the amount X1 of the surfactant remaining in 1 g of the multilayer film was calculated.
[0216] HPLC conditions
[0217] Column used: ZORBAX Eclipse XDB-C8
[0218] Column temperature: 40°C
[0219] Elution solvent: Gradient elution from acetonitrile / ammonium formate to acetonitrile
[0220] Flow rate: 0.5mL / min
[0221] Injection volume: 2 μL
[0222] Detector: Mass spectrometer
[0223] The larger the residual ratio R is, the less likely it is to generate dirt when the layer of the liquid composition is heated and dried. Therefore, the larger the residual ratio R is, the less resinous dirt adheres to the inside of the heating and drying device.
[0224] [Surfactant compositions used in Examples and Comparative Examples]
[0225] The compositions of the surfactant compositions A to G used in the examples and comparative examples are shown in Table 1. In Table 1, compositions A to G refer to surfactant compositions A to G, respectively. Surfactant compositions A to G are commercially available. In Table 1, the values of the surfactant component Mn in compositions F and G are values for components having a number average molecular weight of 500 or less.
[0226] [Table 1]
[0227]
[0228] [Example 1]
[0229] (1-1) Preparation of substrate
[0230] Cycloolefin resin (ZEONOR 1420 manufactured by Zeon Co., Ltd., Japan) pellets were dried at 100°C for 5 hours. The pellets were supplied to an extruder, melted in the extruder, and extruded into a film-like shape from a T-die onto a casting drum through a polymer tube and a polymer filter, and cooled to obtain a long unstretched film (thickness 80 μm, width 1600 mm). A sample of A4 size (about 210 mm × about 297 mm) was cut out therefrom.
[0231] One surface of the cut unstretched film was subjected to discharge treatment using a corona treatment device to prepare a substrate for forming a cured layer of the liquid composition.
[0232] (1-2) Formation of liquid composition layer
[0233] SUPERFLEX 870 (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., ether-based polyurethane, Tg 78° C., solid content 30%) was used as an aqueous dispersion (polyurethane emulsion) of polyurethane, and the aqueous dispersion was collected in an amount of 100 parts of polyurethane. To this aqueous dispersion, 20 parts of glycerol polyglycidyl ether ("Denacol EX-512" manufactured by Nagase ChemteX Co., Ltd.), 8 parts of silica fine particles having an average particle size of 80 nm ("SNOWTEX ZL" manufactured by Nissan Chemical Industries, Ltd.), 2.5 parts of an aqueous dispersion of silica particles ("SNOWTEX MP-2040" manufactured by Nissan Chemical Industries, Ltd.; average particle size 200 nm), a surfactant composition A containing a surfactant having a number average molecular weight of 4660 as a nonionic surfactant and a low molecular weight component (L) having a molecular weight of 500 or less in an amount of 11% of the total, and water were added to obtain a liquid composition having a solid content concentration of 4% containing an uncured polyurethane resin. Here, the amount of the nonionic surfactant composition added was 1.25 wt% relative to the solid content contained in the liquid composition and 500 ppm by weight (0.05 wt%) relative to the liquid composition.
[0234] The liquid composition was applied to the discharge-treated surface of the cut unstretched film as a substrate using a bar coater so as to have a dry thickness of 0.08 μm.
[0235] (1-3) Formation of Solidified Layer of Liquid Composition
[0236] Then, the layer of the liquid composition is dried by heating to form a solidified layer of the liquid composition as a primer layer on the unstretched film. Thus, a multilayer film as an optical film having a solidified layer of a substrate and a liquid composition is obtained. The obtained multilayer film is evaluated according to the above method. The results are shown in Table 2.
[0237] [Examples 2 to 9, Comparative Examples 1 to 2]
[0238] Instead of surfactant composition A, surfactant compositions shown in Tables 2 to 4 were used.
[0239] The addition amount of the surfactant composition was changed to the addition amount shown in Tables 2 to 4.
[0240] Except for the above matters, a multilayer film as an optical film was obtained in the same manner as in Example 1, and evaluation was performed in the same manner as in Example 1. The results are shown in Tables 2 to 4.
[0241] [result]
[0242] The evaluation results are shown in Tables 2 to 4.
[0243] The abbreviations and the like in Tables 2 to 4 have the following meanings.
[0244] “Amount of surfactant composition added”: the amount of surfactant composition added, based on 100% by weight of the liquid composition.
[0245] “Net surfactant addition amount” refers to the amount of surfactant components having a number average molecular weight of more than 500 in the surfactant composition, based on 100% by weight of the liquid composition.
[0246] “Surfactant (N) / component (L)”: the weight ratio of the nonionic surfactant (N) having a number average molecular weight of more than 500 in the surfactant composition added to the liquid composition to the component (L) in the surfactant composition.
[0247] Notes in Table 4 *1: Anionic surfactants are included, and nonionic surfactants (N) are not included.
[0248] Note *2 in Table 4: Nonionic surfactants (N) having a number average molecular weight of more than 500 are not included.
[0249] [Table 2]
[0250]
[0251] [Table 3]
[0252]
[0253] [Table 4]
[0254]
[0255] As shown in the above results, the surfactant residual rate of the liquid composition of the embodiment comprising a nonionic surfactant (N) having a number average molecular weight greater than 500, the weight ratio of the nonionic surfactant (N) to the component (L) being 70 / 30 or more (i.e., comprising 70 parts by weight or more and 100 parts by weight or less of the nonionic surfactant (N) and 0 parts by weight or more and 30 parts by weight or less of the component (L)) is evaluated as good or qualified, and the surface state is evaluated as good or qualified. Therefore, the liquid composition of the embodiment is not prone to volatile dirt when drying, and the surface state of the solidified layer of the liquid composition is good.
[0256] On the other hand, the surface state of the solidified layer of the liquid composition of the liquid composition of Comparative Example 1 using anionic surfactants was poor. In addition, the surfactant residual rate of the liquid composition of Comparative Example 2 using nonionic surfactants having a number average molecular weight of 500 or less was evaluated as poor, indicating that a large amount of volatile dirt was generated during drying.
Claims
1. A liquid composition comprising 70 parts by weight or more and 100 parts by weight or less of a nonionic surfactant having a number average molecular weight greater than 500, 0 parts by weight or more and 30 parts by weight or less of a component having a number average molecular weight of 100 or more and 500 or less, and water.
2. The liquid composition according to claim 1, wherein The number average molecular weight of the nonionic surfactant is 550 or more.
3. The liquid composition according to claim 1, wherein The liquid composition contains 0.02% by weight or more and 0.10% by weight or less of the nonionic surfactant.
4. The liquid composition according to claim 1, wherein The liquid composition also includes polyurethane and silica particles. 5 . An optical film comprising a substrate and a cured layer of the liquid composition according to claim 1 provided on a main surface of the substrate.
6. The optical film according to claim 5, wherein: The substrate is composed of a cycloolefin resin.
Citation Information
Patent Citations
Resin sheet
JP2011184676A
Polymerizable composition and optical anisotropic body prepared therewith
JP2017203168A
Laminate and optical film
US20170351147A1
Polymerizable composition and optically anisotropic body using same
US20180002459A1
Laminate and optical film
WO2016136231A1